Examen especial a las cuentas de compras, ventas e inventarios de la boutique casa valeria, ubicada en la provincia de Cotopaxi, cantón Latacunga. periodo del 1 de enero al 31 de diciembre del 2014 - Cando Santo, Anabel Rocio (2016)
The present work of investigation reviews to the first audit exam applied at Casa Valeria Boutique, as the same that permits to determine the degree of reasonableness of accounting about balances purchases, sales and inventories presented in the corresponding financial statements from January 1st to December 31st, 2014. For the development to the recollected audit true and real information that permits to confirm the procedures applied in the company accounts. According to the applied investigation were deductive….